Shipping the Medieval Military : English Maritime Logistics in the Fourteenth Century. - Lambert, Craig L. (Warfare in history., 2011)
During the fourteenth century England was scarred by famine, plague and warfare. Through such disasters, however, emerged great feats of human endurance. Not only did the English population recover from starvation and disease but thousands of the kingdom's subjects went on to defeat the Scots and the French in several notable battles. Victories such as Halidon Hill, Neville's Cross, Crécy and Poitiers not only helped to recover the pride of the English chivalrous class but also secured the reputation of Edward III and the Black Prince. Yet what has been underemphasized in this historical narra.